ANALYSIS OF FACTORS AFFECTING CONSUMERS IN BUYING KYT BRAND HELMET (Cace Study of Residents in Cawang East Jakarta) - Dewi; Tobing , Fenny BNL; Sihombing, Christina N. (Fundamental Management Journal, 2020)
With the depelopment of technolog, there are many helmet products offered by producers toconsumers. Helmets, which are one of the products with a very rapid increase, have long been recognized by the public, namely the KYT helmet. Judging from the high consumer interest in buying KYT brand helmets, the demand for helmets increasing. The research was conducted on residents in the Cawang Village, Eas Jakarta with primary data sorcesobtained by researchers through a questionnaire distributed to 100 respondents. Meanwhile, secondary data were obtained from literature studies, questionnaires and other sources which are certainly related to this research. This research is quantitative in nature, namely using multiple linier regression analysis,instument testing, validity and reliabilitytesting, hypothesis testing, determintion coefficient test (R²), partial t test, and simultaneous f teston consumer buying decisions. To measure consumer purchasing decisions on the variables of teste, namely: type of model, color, and outer appearance (body), while for the quality variables, namely: comfort and durability. Keywords: type of model, color, and outward appearance (body), while for quality variables, namely: comfort and durability